Noninvasive diagnosis of Helicobacter pylori among patients with dyspepsia - Thapa, Suresh; Thapa, Jiwan; Karki, Binod; Khadka, Dibas; Bhandari Thapa, Anju (Nepal Journal of Medical Sciences, 2020)
Introduction: Helicobacter pylori (H. pylori) infection is a common disease with disparity in geography, age, race and socioeconomic status. Present study aims to assess the accuracy of noninvasive diagnostic tests. Methods: This is a hospital based cross sectional, observational study of 100 dyspeptic patients during November 2017- June 2018. Profile of dyspeptic patients were recorded in a proforma and accuracy of serology and stool antigen test for H. pylori was compared with histology detection in gastric biopsies. Results: Mean age of patients was 39.5±13.7 years with almost equal gender distribution. Prevalence of H. pylori was 56% with dyspeptic symptoms in gastric biopsies. Significant association of the infection was seen in patients with a longer duration of dyspepsia, pangastritis on endoscopy and chronic gastritis on histologic examination. Stool antigen test had good sensitivity (71%) and specificity (82%) for H. pylori detection compared with standard histological diagnosis. Conclusion: Overall prevalence of H. pylori was 56% and was more common in patients of age > 44 years with dyspepsia. Stool antigen has a good diagnostic accuracy and can be used in resource limited settings. However, we recommend a community based study in larger population.